Pelaksanaan Pendidikan Literasi Finansial pada Siswa Sekolah Dasar - Viving Laila; Syamsul Hadi; Subanji Subanji (Pascasarjana Universitas Negeri Malang, 2019)
Abstract: This study discusses how to implement financial literacy education in elementary school students. Financial literacy education is a person's activity in applying, understanding and managing information to make financial decisions. Financial literacy education can be taught early to provide knowledge and skills in improving financial well-being. This study uses a descriptive qualitative approach to describe the activities of teachers and students in the implementation of financial literacy education in elementary schools. This study shows that the implementation of financial literacy education can provide positive attitudes for students to participate in production activities and motivate students to save. Teachers can teach financial literacy education in accordance with the basic competencies that already exist in subjects such as mathematics and social studies. Teachers can teach the material the role of the economy in an effort to improve the lives of the people by introducing the type of business and doing activities to make a work and sell it. Abstrak: Penelitian ini membahas tentang bagaimana melaksanakan pendidikan literasi finansial pada siswa sekolah dasar. Pendidikan literasi finansial merupakan aktivitas seseorang dalam mengaplikasikan, memahami, dan mengelola informasi untuk membuat suatu keputusan finansialnya. Pendidikan literasi finansial dapat diajarkan sejak dini untuk memberikan pengetahuan dan keterampilan dalam meningkatkan kesejahteraan finansialnya. Penelitian ini menggunakan pendekatan kualitatif jenis deskriptif, untuk mendeskripsikan aktivitas guru dan siswa dalam pelaksanaan pendidikan literasi finansial di sekolah dasar. Penelitian ini menunjukkan bahwa pelaksanaan pendidikan literasi finansial dapat memberikan sikap positif siswa untuk berpartisipasi dalam kegiatan produksi dan memotivasi siswa untuk menabung. Guru dapat mengajarkan pendidikan literasi finansial sesuai dengan kompetensi dasar yang sudah ada pada mata pelajaran, seperti Matematika dan IPS. Guru dapat mengajarkan materi peran ekonomi dalam upaya menyejahterakan kehidupan masyarakat dengan mengenalkan jenis usaha serta melakukan kegiatan membuat sebuah karya dan menjualnya.